Dietary intake of glucoraphanin prevents the reduction of dopamine transporter in the mouse striatum after repeated administration of MPTP - Yaoyu Pu; Youge Qu; Lijia Chang; Si‐ming Wang; Kai Zhang; Yusuke Ushida; Hiroyuki Suganuma; Kenji Hashimoto (Wiley, 2019)
Abstract Aims Parkinson's disease (PD) is a chronic and progressive neurodegenerative disorder. Although diet may influence the development of PD, the precise mechanisms underlying relationship between diet and PD pathology are unknown. Here, we examined whether dietary intake of glucoraphanin (GF), the precursor of a natural antioxidant sulforaphane in cruciferous vegetables, can affect the reduction of dopamine transporter (DAT) in the mouse striatum after repeated administration of MPTP (1‐methyl‐4‐phenyl‐1,2,3,6‐tetrahydropyridine). Methods Normal food pellet or 0.1% GF food pellet was given into male mice for 28 days from 8‐week‐old. Subsequently, saline (5 mL/kg × 3, 2‐hour interval) or MPTP (10 mg/kg × 3, 2‐hour interval) was injected into mice. Immunohistochemistry of DAT in the striatum was performed 7 days after MPTP injection. Results Repeated injections of MPTP significantly decreased the density of DAT‐immunoreactivity in the mouse striatum. In contrast, dietary intake of 0.1% GF food pellet significantly protected against MPTP‐induced reduction of DAT‐immunoreactivity in the striatum. Conclusion This study suggests that dietary intake of GF food pellet could prevent MPTP‐induced dopaminergic neurotoxicity in the striatum of adult mice. Therefore, dietary intake of GF‐rich cruciferous vegetables may have beneficial effects on prevention for development of PD.